Comparative transcriptome profiling reveals the importance of GmSWEET15 in soybean susceptibility to Sclerotinia sclerotiorum - Kunqin Xiao; Kaibin Qiao; Wenjing Cui; Xun Xu; Hongyu Pan; Fengting Wang; Shoudong Wang; Feng Yang; Yuanhu Xuan; Anmo Li; Xiao Han; Zhuojian Song; et al. (Frontiers in Microbiology, 2023)
Soybean sclerotinia stem rot (SSR) is a disease caused by Sclerotinia sclerotiorum that causes incalculable losses in soybean yield each year. Considering the lack of effective resistance resources and the elusive resistance mechanisms, we are urged to develop resistance genes and explore their molecular mechanisms. Here, we found that loss of GmSWEET15 enhanced the resistance to S. sclerotiorum, and we explored the molecular mechanisms by which gmsweet15 mutant exhibit enhanced resistance to S. sclerotiorum by comparing transcriptome. At the early stage of inoculation, the wild type (WT) showed moderate defense response, whereas gmsweet15 mutant exhibited more extensive and intense transcription reprogramming. The gmsweet15 mutant enriched more biological processes, including the secretory pathway and tetrapyrrole metabolism, and it showed stronger changes in defense response, protein ubiquitination, MAPK signaling pathway-plant, plant-pathogen interaction, phenylpropanoid biosynthesis, and photosynthesis. The more intense and abundant transcriptional reprogramming of gmsweet15 mutant may explain how it effectively delayed colonization by S. sclerotiorum. In addition, we identified common and specific differentially expressed genes between WT and gmsweet15 mutant after inoculation with S. sclerotiorum, and gene sets and genes related to gmsweet15_24 h were identified through Gene Set Enrichment Analysis. Moreover, we constructed the protein–protein interaction network and gene co-expression networks and identified several groups of regulatory networks of gmsweet15 mutant in response to S. sclerotiorum, which will be helpful for the discovery of candidate functional genes. Taken together, our results elucidate molecular mechanisms of delayed colonization by S. sclerotiorum after loss of GmSWEET15 in soybean, and we propose novel resources for improving resistance to SSR.